Sismicidad del Golfo de Cádiz y zonas adyacentes - Martín Dávila, J.; Pazos, A. (Física de la Tierra, 2003)
Main characteristics of seismicity at Gulf of Cadiz and boundary regions have been summarised in this paper, selecting a zone between latitudes 34º and 38º North and longitudes 6º and 12º West, surrounding the above mentioned Gulf by the Southern part of Iberian Peninsula, the north-western part of Africa and, to the West, by a marine area including Gorringe bank. To study those characteristics, seismicity has been represented on maps at surface level and in depth, both in two and three dimensions.